Completion of the Common Internal Market of Recycling in the EU - Position of New Member States - Wysokińska, Zofia (Comparative Economic Research. Central and Eastern Europe, 2011)
In the paper will be presented the analysis of ecological competitiveness in the EU ("old" and "new" Member States) recycling market within the process of the establishment of common standards related to the Prevention and Recycling of Waste. The paper examined advantages of common standards for Europe from the point of view of the completion of the common internal market of recycling within the EU Strategy promoting the sustainable growth.